x-7=-13+13x

Simple and best practice solution for x-7=-13+13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-7=-13+13x equation:


Simplifying
x + -7 = -13 + 13x

Reorder the terms:
-7 + x = -13 + 13x

Solving
-7 + x = -13 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-7 + x + -13x = -13 + 13x + -13x

Combine like terms: x + -13x = -12x
-7 + -12x = -13 + 13x + -13x

Combine like terms: 13x + -13x = 0
-7 + -12x = -13 + 0
-7 + -12x = -13

Add '7' to each side of the equation.
-7 + 7 + -12x = -13 + 7

Combine like terms: -7 + 7 = 0
0 + -12x = -13 + 7
-12x = -13 + 7

Combine like terms: -13 + 7 = -6
-12x = -6

Divide each side by '-12'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| x+2=x-1/4 | | 10(g-5)=-80 | | 175000.00+550.00x=300440.00 | | x+3x=50 | | x+8+x=16 | | -9=-3x+x+3 | | ((32x^3)-(28x^2)-47x-12)=0 | | (-5/2x)+(3/4x)=(-3/4) | | 2(-1-1x)=-26 | | ((32x^3)-(28x^2)-47x-12)/(8x+3) | | 2x+7=4x+65/9 | | 7x+1=-3x-19 | | -2x+2-x=32 | | 4x+2-x=29 | | 8x-2(x+5)-7+5x=-21+4+x | | 10+4x-x=64/7 | | 8x-2(x-5)-7+5x=21+3x | | -3+4x-7x=21 | | 118=4(20)+38 | | 8d-3/5=5d+3/2 | | 51=2x+7x+6 | | p=23/3(18) | | 106/5=7x+4x-4/5 | | p=7(18) | | 10x+7=20x | | p=6(18) | | 6a-4a-5=7a-23 | | -7x+6x=-2 | | (7u-4v-2)(2u+1)=0 | | x+10=9-1 | | -2x-2-2x=26 | | Y=50.8y |

Equations solver categories